Populasi Kepiting Bakau (Scylla serrata) di Perairan Muara Sungai Barumun Kabupaten Labuhanbatu Ditinjau dari Pola Pertumbuhan dan Faktor Kondisi - Indah Pratiwi; Rivo Hasper Dimenta (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Mangrove crab (Scylla serrata) is one of the prima donna sources of protein caught by fishermen around mangrove forest waters in the waters of the Barumun River Estuary, Labuhanbatu Regency. This study aims to inform about condition factors, growth patterns of crab populations, and reproductive aspects in the form of abundance of Gonad Maturity Level (TKG). Determination of 3 sampling points is done by using purposive random sampling method. Scylla serrata sampling was carried out using Bubu. Data analysis presents information on the abundance of gonadal maturity level, growth pattern, and Fulton condition factor (K), which is presented quantitatively. The results showed that male and female Scylla serrata growth patterns were categorized as negative allometric b < 3, with carapace width growth being faster than weight gain. Fulton condition factor (K) values obtained ranged from 50.14-132.75 for male Scylla serrata, and female ranged from 80.34-123.94. The gonadal maturity level of Scylla serrata was dominated by TKG II crabs, and the lowest abundance of gonad maturity was in TKG IV crabs. This indicates that, in December-February, the condition of the Scylla serrata population around the mangrove forest waters of the Barumun river estuary, is predicted to be in the stage of adult dominance that is ready to reproduce and prepare to spawn.